DNA barcoding of the Italian anecic Octodrilus species in rural (vineyard) and forested areas with description of Octodrilus zicsiniello sp. nov. (Clitellata, Megadrili) - Csuzdi, Csaba; Szederjesi, Tímea; Marchán, Daniel Fernández; Sosa, Irene De; Gavinelli, Federico; Dorigo, Luca; Pamio, Alberto; Dreon, Angelo Leandro; Fusaro, Silvia; Moretto, Enzo; Paoletti, Maurizio Guido (Zootaxa, 2018)
DNA barcoding of 172 anecic Octodrilus specimens collected in NE Italy and bordering Croatia has been carried out. The Bayesian phylogenetic tree showed high support for almost all currently recognized species, however, some unexpected results also appeared. The clade representing Oc. pseudocomplanatus contains a highly advanced subclade, which morphologically resembles Oc. slovenicus. The highly supported Oc. tergestinus clade consists of four unresolved divergent lineages of which the first corresponds to Oc. istrianus and the second resembles Oc. mimus morphologically; the third and fourth clades show typical tergestinus characters. The widely distributed Oc. complanatus consists of three highly divergent subclades which are sister to a new species, Oc. zicsiniello sp. nov., hereunder described.